Public Management of Solid Waste in the Field of Education (Research, Society and Development, 2022)
The objective of this research was to diagnose the current solid waste management model in public schools in the city of Caicó-RN, through the identification of activities and sources that generate these types of waste, their characterization and classification, so that a plan can be proposed. management of these polluting residues in the studied educational institutions. The studies were developed in partnership with the Department of the Environment of the municipality of Caicó, RN. Visits were conducted in twenty-three municipal public schools, conducting a survey of the reality of the solid waste management system in such teaching institutions. This diagnosis was conducted through activities related to waste management in public schools, such as: application of questionnaires, on-site investigation, photographs of the temporary storage of waste generated, and interviews with professionals from the sectors responsible for handling waste. The results showed that in the public schools studied in the municipality of Caicó-RN, there is no environmental management program for solid waste management, and that only four institutions have any activity related to this topic, and the municipality should guarantee the separation and forwarding these materials to be reused and/or recycled, thus ensuring a sustainable educational environment and effective environmental education.